Evaluation of serum vitamin B12 levels in patients with COVID-19 infection: A case-control study: Evaluation of serum vitamin B12 in patients with COVID-19 - Sezgin, Yılmaz (Journal of Medical Biochemistry, 2023)
Background: COVID-19 disease affects the respiratory and cardiovascular systems. Vitamin B12 has been associated with A1AT, one of the protective factors of lung tissue, and homocysteine among the cardiovascular risk factors. Therefore we suggest that low vitamin B12 levels are associated with a disposition to COVID-19 infection. This study aims to determine whether there is a relationship between COVID-19 infection and serum vitamin B12 levels. Methods: This research is a case-control study. Seventy-six people with COVID-19 constituted the case group. Seventy-six people without COVID-19 formed the control group. Vitamin B12 and homocysteine levels of 152 patients included in the study were analyzed. Results: The odds ratio for vitamin B12 was 0.99 (0.978-0.995). When the value of the vitamin B12 variable decreases by one unit, the risk of COVID-19 increases by 1%. The odds ratio for homocysteine was 1.81 (1.414-2.325). When the value of the homocysteine variable increases by one unit, the risk of COVID-19 increases by 1.81 times. According to ROC analysis, when serum vitamin B12 is below 222.5 ng/L and homocysteine is above 13.7 umol/L, it may increase the risk of COVID-19. Conclusions: We suggest that patients with low vitamin B12 levels and high homocysteine levels are more severely affected by COVID-19 infection.
Keywords: COVID-19; Vitamin B12 deficiency; Homocysteine